Neuromyelitis optica: a positive appraisal of seronegative cases. (16th February 2015) - Bernard‐Valnet, R.; Liblau, R. S.; Vukusic, S.; Marignier, R.
Abstract : Neuromyelitis optica (NMO) is a rare inflammatory disorder of the central nervous system. The hallmark of NMO is the presence of specific autoantibodies directed against aquaporin 4 (AQP4‐IgG). AQP4‐IgG, included in diagnostic criteria, has enlarged the clinical spectrum of NMO and serves to predict relapses. Moreover AQP4‐IgG has provided unprecedented insight in the immunopathology of NMO, representing a rationale for therapeutic intervention with relevant novel treatment strategies specific for NMO. However, some patients remain seronegative for AQP4‐IgG despite a definite diagnosis of NMO and the use of the finest methods for antibody detection. Interestingly, seronegative NMO (NMO neg ) patients exhibit different demographic and disease‐related characteristics in comparison to seropositive patients. The recent association with autoantibodies specific for myelin oligodendrocyte glycoprotein (MOG) is the main indication that disease mechanisms might differ in NMO pos and NMO neg, challenging the position of NMO neg patients in the spectrum of demyelinating diseases and therapeutic strategies to be adopted. Thus, a reappraisal of the NMO neg population is needed to improve NMO care. Here the current knowledge regarding NMO neg is reviewed and hypotheses on its pathogenesis are made including a comprehensive description of detection methods and the prevalence of AQP4‐IgG and a review of the epidemiological, clinical and paraclinical characteristics of NMO neg ; finally an integrated view of the general pathophysiological mechanisms underlying NMO neg is provided.